Efficacy of Picosecond Laser in Clinical, Histopathology, and Immunohistochemistry Examination in Indonesian Wrinkled Skin: Efficacy of picosecond laser - Wardhani, Putri Hendria; Prakoeswa, Cita Rosita Sigit; Listiawan, Muhammad Yulianto (Journal of Lasers in Medical Sciences, 2024)
Introduction: The elderly population wants to improve skin function and maintain a youthful appearance without wrinkles. Laser is one of the highly developed and widely used therapeutic modalities for skin aging, as it stimulates dermal collagen formation. Picosecond laser therapy is performed on skin with wrinkles to determine the mechanism of wrinkle improvement with a picosecond laser through an increase in tissue inhibitor of metalloproteinases 1 (TIMP-1), and a decrease in matrix metalloproteinase-1 (MMP-1), which was confirmed by collagen density. Methods: The study was started from March 2021 to July 2021 at URJ Dr. Soetomo Hospital Surabaya and Surabaya Skin Centre. Twenty patients meeting the inclusion criteria of being 36-55 years of age and having a wrinkle in the forearm were enrolled by random sampling. Each sample data was recorded, the average TIMP-1, MMP-1, collagen density, and clinical wrinkles were calculated, and the laser was performed using a picosecond 755 nm laser. Results: All patients showed a moderate pre-test wrinkle scale. The figure for TIMP-1 and MMP1 after therapy was higher. The MMP-1/TIMP-1 ratio in wrinkles treated by using a picosecond laser was lower but insignificant than before. The picture of collagen density indicates that collagen density after laser therapy was higher than before. Conclusion: The result of clinical examination, histopathology, and immunohistochemistry in this research explained that a picosecond 755 nm laser with DLA is an effective therapy for wrinkles in Indonesian patients without any adverse effects.